MANAGING CULTURAL DIVERSITY IN THE CLASSROOM - Khanyile, Thembisile (Journal of Community and Health Sciences, 2020)
Introduction: This article focus on the cultural issues challenging health professional academics in this era of transformation in South Africa. Objectives: The objective is to discuss various concepts of cultural diversity and the management thereof. Methods: Review of literature on the management of cultural diversity. Conclusion: The education and training programs for health professionals should lead to affirmation of cultural diversity and promote respect for the person while leading to tolerance of different views and ideas.